2021
DOI: 10.3390/ijms221810062
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Brevifolincarboxylate Attenuates Free Fatty Acid-Induced Lipid Metabolism and Inflammation in Hepatocytes through AMPK/NF-κB Signaling Pathway

Abstract: The prevalence of non-alcoholic fatty liver disease (NAFLD) is one of the leading causes of chronic liver diseases worldwide. This study examined the potential protective effects of a naturally occurring polyphenolic compound, methyl brevifolincarboxylate (MBC) on fatty liver injury in vitro. The results showed that MBC at its non-cytotoxic concentrations, reduced lipid droplet accumulation and triglyceride (TG) levels in the oleic acid (OA)-treated human hepatocarcinoma cell line, SK-HEP-1 and murine primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…2 b). Numerous studies have shown a crucial role for the AMPK/CPT1 pathway in inflammatory diseases [ 31 ]. In this study, we hypothesized that l -carnitine induced CPT1 upregulation mediated by AMPK in the LPS-stimulated FLS model.…”
Section: Resultsmentioning
confidence: 99%
“…2 b). Numerous studies have shown a crucial role for the AMPK/CPT1 pathway in inflammatory diseases [ 31 ]. In this study, we hypothesized that l -carnitine induced CPT1 upregulation mediated by AMPK in the LPS-stimulated FLS model.…”
Section: Resultsmentioning
confidence: 99%
“…Free fatty acids derived from adipose tissue breakdown serve as natural nuclear receptor ligands and play a major role in the regulation of NASH-related lipid metabolism and inflammation ( Yadati et al, 2021 ). Polyunsaturated fatty acids and their derivatives could activate peroxisome proliferator-activated receptor-α (PPARα), which could induce the expressions of genes involved in fatty acid oxidation and insulin sensitivity, and downregulate nuclear factor κB (NF-κB) level ( Geethangili et al, 2021 ; López-Salazar et al, 2021 ). However, in a mouse model of NASH, a diet fed polyunsaturated fatty acids activates PPARα signaling and inhibits hepatic de novo fat synthesis, but does not prevent steatohepatitis ( Ishida et al, 2021 ), which is likely to high levels of hepatic lipid peroxidation in this model abolished the protective effect of PPARα activation and resulted in lipotoxic hepatocyte injury and inflammatory cells recruitment.…”
Section: Intrahepatic Factors In Nashmentioning
confidence: 99%
“…In addition, they can decrease both serum and liver proinflammatory cytokines that contribute to the fatty liver [ 104 ]. Treatment with methyl brevifolincarboxylate, a natural polyphenolic compound, reduced lipid metabolism and inflammatory markers, such as TNF-α, IL-6, and IL-1β, via modulating 5′ adenosine monophosphate-activated protein kinase (AMPK)/NF-κB signaling pathway [ 105 ]. However, clinical studies are still needed to confirm the function of polyphenols.…”
Section: Treatment Options For Nafld and Nash Based On Modulation Of Gut Microbiota Intrahepatic Immunity And Metabolic Signaling Pathwaymentioning
confidence: 99%